INVENTORY OF SEA CUCUMBER SPECIES (Holothuroidea) IN THE WATERS OF PANDARATAN BEACH SARUDIK DISTRICT, CENTRAL TAPANULI REGENCY, NORTH SUMATRA - Panggabean, Iis Apriati; Samiaji, Joko; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2021)
Pandaratan Beach is one of the beaches located in Central Tapanuli Regency, North Sumatra. Pandaratan Beach has a diverse potential of biological resources namely mangrove ecosystems, seagrass ecosystems, and coral reef ecosystems. Sea cucumbers are among the potentials in the beach.This research was conducted in February 2021. The purpose of this study is to find out the type, abundance and diversity of sea cucumbers in the waters of Pandaratan Beach. The method used was the survey and for the determination of the observation location was determined by purposive sampling. The results showed that 1 genera and 3 species of sea cucunbers were found, namely Holothuria scabra, Holothuria atra, and Holothuria leucospilota. The abundance of sea cucumbers ranged from 444 – 800 ind/ha.The highest relative abundance was found in the found in the species of Holothuria leucospilota at station I with a percentage of 66.67%. The sea cucumber diversity index ranged from 0.6515 - 1.1955.